Structural To Functional Transformation: Policy Evaluation at KWBC Sumbagtim in Customs and Excise Services - Faras Tampani; Tien Yustini (Jurnal Indonesia Sosial Teknologi, 2024)
Bureaucratic reform has been an important focus of many countries facing the complexity of public administration issues. Indonesia, as a country with a complex and prolix bureaucracy, is no exception. To simplify and improve bureaucratic efficiency, the Indonesian government, through the Ministry of State Apparatus Utilization and Bureaucratic Reform, implemented a policy of transforming structural positions into functional positions. This research aims to analyse the effectiveness of the transformation policy of structural positions to functional positions of employees within the Customs and Excise Regional Office (KWBC) Sumbagtim and its impact on improving service quality. The research method uses a qualitative approach through interviews, observation and document analysis. The type of qualitative research used is a case study, a research strategy in which researchers carefully investigate phenomena by implementing specific programs, unique events, implementing activities, or a process that occurs in a group of individuals. The data collection method used in this research refers to the results of in-depth interviews, observation, and document analysis. The results showed that the structural transformation to functional positions has significantly changed the quality of KWBC Sumbagtim services. Although some employees faced difficulties adapting to the process, this policy positively impacted service efficiency, responsiveness, and accuracy.